Indene Compounds Synthetically Derived from Vitamin D Have Selective Antibacterial Action on Helicobacter pylori. Issue 4 (16th May 2018) - Wanibuchi, Kiyofumi; Hosoda, Kouichi; Ihara, Masato; Tajiri, Kentaro; Sakai, Yuki; Masui, Hisashi; Takahashi, Takashi; Hirai, Yoshikazu; Shimomura, Hirofumi
Abstract: Helicobacter pylori infects the human stomach and is closely linked with the development of gastric cancer. When detected, this pathogen can be eradicated from the human stomach using wide‐spectrum antibiotics. However, year by year, H. pylori strains resistant to the antibacterial action of antibiotics have been increasing. The development of new antibacterial substances effective against drug‐resistant H. pylori is urgently required. Our group has recently identified extremely selective bactericidal effects against H. pylori in (1R, 3aR, 7aR)‐1‐[(1R)‐1, 5‐dimethylhexyl]octahydro‐7a‐methyl‐4 H ‐inden‐4‐one (VDP1) (otherwise known as Grundmann's ketone), an indene compound derived from the decomposition of vitamin D3 and proposed the antibacterial mechanism whereby VDP1 induces the bacteriolysis by interacting at least with PtdEtn (dimyristoyl‐phosphatidylethanolamine [di‐14:0 PtdEtn]) retaining two 14:0 fatty acids of the membrane lipid constituents. In this study, we synthesized new indene compounds ((1 R, 3a R, 7a R )‐1‐((2 R, E )‐5, 6‐dimethylhept‐3‐en‐2‐yl)‐7a‐methyloctahydro‐4 H ‐inden‐4‐one [VD2‐1], (1 R, 3a R, 7a R )‐1‐(( S )‐1‐hydroxypropan‐2‐yl)‐7a‐methyloctahydro‐1 H ‐inden‐4‐ol [VD2‐2], and (1 R, 3a R, 7a R )‐7a‐methyl‐1‐(( R )‐6‐methylheptan‐2‐yl)octahydro‐1 H ‐inden‐4‐ol [VD3‐1]) using either vitamin D2 or vitamin D3 as materials. VD2‐1 and VD3‐1 selectively disrupted the di‐14:0 PtdEtn vesicles without destructing the vesicles of PtdEtn (dipalmitoyl‐phosphatidylethanolamine) retaining two 16:0 fatty acids. In contrast, VD2‐2, an indene compound lacking an alkyl group, had no influence on the structural stability of both PtdEtn vesicles. In addition, VD2‐1 and VD3‐1 exerted extremely selective bactericidal action against H. pylori without affecting the viability of commonplace bacteria. Meanwhile, VD2‐2 almost forfeited the bactericidal effects on H. pylori . These results suggest that the alkyl group of the indene compounds has a crucial conformation to interact with di‐14:0 PtdEtn of H. pylori membrane lipid constituents whereby the bacteriolysis is ultimately induced.